Corneal transplantation during COVID-19 pandemic: need for special considerations-A live review - Anuj Kumar Pandey; Nidhi Mudgil; Yogesh Wadgave; Sidharth Sekhar Mishra (AIMS Press, 2021)
Corneal blindness is the fourth leading cause of blindness worldwide, with 10 million people having bilateral corneal blindness, nearly 80% of all corneal blindness cases are avoidable and are reversible. Corneal transplantation (CT) is the most frequently performed type of transplant across the world. This review was conducted with the objective of identifying if it is safe to harvest the cornea from the patients died due to COVID-19 and preventing the chances of transmission from donor to the recipient or healthcare worker handling the harvested cornea. A total of 45 articles were found with the keywords and out of all, only 16 fulfilled the inclusion criteria. RT-PCR is the technique of choice for detection of virus in the corpse and the sample analyzed was a pharyngeal swab. Available literature states unavailability of sufficient evidence-based studies proving presence of virus in the cornea or tear of COVID affected patients There is no proven consensus on presence of Virus in cornea. It is important to follow preferred practice guidelines so as to restart eye banking and do at least the emergency surgeries without having risk of disease transmission and keeping ourselves safe.